Isolation and identification of novel casein-derived bioactive peptides and potential functions in fermented casein with Lactobacillus helveticus - Mengzhu Fan; Tingting Guo; Wanru Li; Jing Chen; Fushuo Li; Chao Wang; Yi Shi; David Xi-an Li; Shaohui Zhang (Food Science and Human Wellness)
The present study here establishes a complete and effective method for isolating, purifying and identifying extracellular and intracellular peptides, and also describes the characters and bioactivities of peptides from fermented casein with Lactobacillus helveticus. Intracellular peptides are much larger in quantity and more complex in composition than extracellular peptides, between which the correlation reveals proteolytic and metabolic mechanisms.In addition, totally 241 different peptide sequences were identified by Nano LC–MS/MS from casein (212) and Lactobacillus helveticus proteins (29). These casein-derived peptides mostly originated from β-casein, followed by αS1-casein, κ-casein, and αS2-casein, and came from extracell (69) and intracell (143), in which common peptides have a total of 27. Forty-four of the identified peptides were previously described as bioactive, including angiotensin-converting enzyme (ACE)-inhibitory, antioxidant, immunomodulating, antimicrobial, DPP-IV inhibitory, antiamnesic and anticancer effects and so on. Thirteen peptides with the potential of some biological activities are obtained, which were described in previous studies. A total of 47 novel peptides of 5 to 26 amino acids that were not disclosed were obtained. The new sources of natural bioactive peptides may have the very high application value as potential new peptide drugs for treatment human diseases. The product peptide DELQDKIHPF found in both extracell and intracell was quantitatively analyzed using the MRM mode of UPLC-U3Q, 23.1 and 9.76 ng/mL, respectively. The quantitative analysis of the potential bioactive peptide may also advance the production of peptide products in the future. Keywords: Bioactive peptide, Peptide profiling, Fermented casein, Lactobacillus helveticus